KEPRAKTISAN BAHAN AJAR BERBASISE-LEARNING UNTUK MATA KULIAH KALKULUS PEUBAH BANYAK 1 (KPB 1) - ISRA NURMAI YENTI (Ta'dib, 2014)
This research was done to see the practicability of learning material based E-Learning that was developed in Kalkulus Peubah Banyak 1 (KPB 1). The practicability of this material was seen from the easiest of using this material by the students. The design of this research was research development. The research instrument was interview. The data from interview was analyzed by using descriptive analysis. Based on the analysis of interview to the students, it was known that the learning material based E-Learning that was developed was practicable in side of use, the content, and the easiest of using it.Kata kunci: praktis, bahan ajar, e-learning.